Pengembangan Sistem Aplikasi Manajemen Unit Transfusi Darah (UTD) PMI Malang - Tafarrara Irsa Shabrina; Nurudin Santoso; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Blood transfusion unit is a container of medical services to the communit in order to help the communit associated with something about blood. To help the communit and hospitals in resolve the problem, such as a blood request from hospitals using different ways between UTD branch and who do not have UTD branch, there are no details of the number of existing blood stock in Malang Central UTD, and the lack of transparenc of the management process from the initial application blood request until it is received, and blood donation is done manually. The given solution is create a data blood request, leveler or see an urgenc of the request, providing information about blood stock in real time, the existence of a blood deliver to the transparenc of the blood up to the hospital, minimize time in the process of filing blood donation and get an accurate information about blood request if a blood stock are not available in UTD. The system will appl the waterfall model for the process of development. Results of unit testing, integration testing and validation testing yields a value of 100% valid. The compatibilit testing resulted that the system can run on browser type.